Mangrove Ecosystem Conservation Efforts: A Case Study of The Minajadri Monitoring Community Group in Pasir Putih Coastal Area, Cilamaya Kulon, Karawang - Harsanto Mursyid; Kafa Abdallah Kafaa; Situt Setiawan; Annisa Ghinda Agri Utami; Anindita Dian Safira; Tabita Titah Dewanti; Clara Yolandika (Future Science, 2022)
Climate change has become an issue that is often discussed by many parties. One of the impacts is the erosion of the coast by sea waves. A group of environmentally conscious in Karawang are trying to reduce erosion by replanting damaged mangroves as a form of adaptation to environmental changes. The purpose of this paper is to reveal the results of mangrove planting carried out to reduce erosion by seawater. This study employs convergent parallel mixed-methods data collection, which included observation, and mapping with Google Earth and Landsat 8 satellite imagery. Semi-structured interviews with relevant key informants, and literature review. Afterward, descriptive techniques are used to analyze the data/ The findings of this study show that community-led mangrove revegetation initiatives have been successful in reducing seawater abrasion. An area of roughly 6.29 ha with a high-density level makes up the mangrove forest that has been successfully revegetated. It has also evolved into a habitat for numerous mangrove species. Additionally, the community practices ecotourism by using mangrove vegetation. On the other hand, the community's revegetation efforts are highly distinctive, notably by adding sand from sedimentation to generate additional land that is used by the community to build buildings, which may lead to future land ownership rights issues.